2005
DOI: 10.1007/s00384-005-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

The duration of postoperative ileus after elective colectomy is correlated to surgical specialization

Abstract: Restoration of normal intestinal function after elective open colectomy takes 3 (PG) to 4 (PS) days. In our series, specialized training in colorectal surgery has a positive impact on the duration of postoperative ileus. Surgical specialization should be considered an important parameter in future clinical trials aiming to minimize postoperative ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Neither the type of surgery nor the level of training of the operating surgeon was different. Gervaz et al reported of earlier return of gastrointestinal function if the procedure was performed by a specialist colorectal surgeon compared to general surgeons [31]. Unfortunately, there is no mentioning of duration of surgery in their study.…”
Section: Discussionmentioning
confidence: 86%
“…Neither the type of surgery nor the level of training of the operating surgeon was different. Gervaz et al reported of earlier return of gastrointestinal function if the procedure was performed by a specialist colorectal surgeon compared to general surgeons [31]. Unfortunately, there is no mentioning of duration of surgery in their study.…”
Section: Discussionmentioning
confidence: 86%
“…Of the 11 studies comparing outcomes for attending surgeons with versus without fellowship training, two found no difference between groups for patient mortality. One study found decreased survival in patients undergoing aortic aneurysm repair, treated by a general surgeon rather than a vascular or cardiothoracic fellowship‐trained surgeon.…”
Section: Resultsmentioning
confidence: 99%
“…There were three different types of comparison used in the 23 studies. Eleven studies compared patient outcomes achieved by attending surgeons with versus those without fellowship training in their specialist field. Six studies compared patient outcomes for centres with affiliated fellowship training programmes with those without, or outcomes for a single centre before and after the introduction of a fellowship programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study of 88 abdominal surgery patients found that the duration of POI correlates with total surgery time, blood loss and total opiate dose [19]. Gervaz et al [20] studied 124 patients undergoing laparotomy for colectomy (median age, 68 years) and found the duration of ileus significantly reduced in those cases performed by a colorectal surgeon and when opioid analgesia lasted for less than 2 days.…”
Section: Poi: Who Is At Risk?mentioning
confidence: 99%